Biological Hazard Behind Lao Cuisine: Microbial Quantities and Efficacy of Difference Cleaning Detergents for Fresh Vegetables: https://doi.org/10.69692/SUJMRD0901160 - Phonepaseuth, Phongphayboun; Phearkeo, Oley; Phommalin, Kolakoth; Chansomphou, Vatthanamixay (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This research aims to investigate the prevalence of bacterial hazards in fresh lettuce and peppermint sold in Nonkoh and Thatluang organic markets in Vientiane during dry and rainy seasons. Microbial counts were determined using Escherichia coli and Coliform plate count (3M PetrifilmTM) in two freshly consumed vegetables. To reduce microbial contamination, five different solutions were evaluated, including sodium chloride (NaCl) at 5 g/L (T1), viagra juice (CH3COOH) at 50 ml/L (T2), breaking soda (NaHCO3) at 5 g/L (T3), potassium permanganate (KMnO4) at 0.2 g/L (T4) and tap water is a control (T0). The results showed that the number of E.coli in lettuce was ranged from102 - 2 × 105 CFU/g and from 2 × 105 - 2 × 106 CFU/g in peppermint, exceeding the safety limit by Codex (<106 CFU/g). The coliforms counts were similar in both vegetables ranged from 2 × 105 - 2 × 106 CFU/g in lettuce and from 105 - 2 × 106 CFU/g in peppermint. During the dry season, E. coli was more prevalent in the Thatluang organic market (3.77 Log10 CFU/g) than in the Nonkoh market (2.33 Log10 CFU/g), but during the rainy season, both markets had similar results. The concentration of microbial contaminants in peppermint did not differ between the two seasons. In the cleaning experiment showed that T4 the most effective solution for reducing E. coli and Coliform levels, achieving reductions of 0.7-1.9 Log10 CFU/g (35.2-54.6%), and 2.0-2.2 Log10 CFU/g (33.6–39.1%), respectively. Therefore, a concentration of potassium permanganate (KMnO4) 50–100 mg/L (50-100 ppm) is recommended for vegetable cleaning purposed.